Federal Taxation of Income from the Production of Minerals - Kelley, Arthur C. (Journal of Political Economy, 1921)
The policy of post-war taxation which is adopted by the federal government probably will have a more direct and vital influence on the general well-being of the country than any other governmental domestic policy. The war is over but not yet paid for, and it will be many years before the huge national debt of some twenty-four billions of dollars is liquidated. It is, therefore, of prime importance to every citizen to consider without prejudice what is the most equitable and least oppressive method of raising the enormous funds necessary to meet the greatly increased operating expenses of government, interest on the public debt, and the sinking fund to redeem it.